The impact of mobile phones on high school students: connecting the research dots - Sadiq, Sana; Anasse, Khadija; Slimani, Najib (Technium Social Sciences Journal, 2022)
Due to the ubiquity of mobile phones throughout the world, there have been extensive scholarly research on their impact within and across areas. Researchers have looked at the impact of this device from different angles, and many scholars have been concerned with the extent to which its usage affects students’ academic performance, particularly in high-school. Several scholars (Kevin Thomas and Marco A. Munoz, 2016, Hosoglu, 2019) have probed the topic using different databases, but the present paper is one of the few to examine Scopus, Science Direct, Web of Science and Cairn with a two-fold aim, namely to summarize the state-of-the-art in this subject area, and, most importantly, to discuss the researchers’ attitudes. 70 articles from the three databases were selected following the PRISMA guidelines to investigate the researchers’ decade-long trends in the literature. We discerned different attitudes and results vis-a-vis the mobile phone impact depending on the variables treated and the location of the study.